Are Movement Artifacts in Magnetic Resonance Imaging a Real Problem?—A Narrative Review - Havsteen, Inger; Ohlhues, Anders; Madsen, Kristoffer H.; Nybing, Janus Damm; Christensen, Hanne; Christensen, Anders (Frontiers in Neurology, 2017)
1. Abstract Movement artefacts compromise image quality and may interfere with interpretation, especially in MRI applications with low signal to noise ratio such as functional MR or diffusion tensor imaging, and when imaging small lesions. High image resolution has high sensitivity to motion artefacts, and often prolongs scan time that again aggravates movement artefacts. During the scan fast imaging techniques and sequences, optimal receiver coils, careful patient positioning and instruction may minimize movement artefacts. Physiological noise sources are motion from respiration, flow and pulse coupled to cardiac cycles, from the swallowing reflex and small spontaneous head movements. Par example, in resting state functional MRI spontaneous neuronal activity adds 1-2% of signal change, even under optimal conditions signal contributions from physiological noise remain a considerable fraction hereof. Movement tracking during imaging may allow for prospective correction or postprocessing steps separating signal and noise.